Biografi Yusrizal dan Pengembangan Batik Tulis Salingka Tabek di Kabupaten Solok Tahun 2017–2025 - Zairifa Maulana; Najmi Najmi (Jurusan Sejarah FIS UNP, 2026)
This study examines the role of Yusrizal in developing Batik Tulis Salingka Tabek in Nagari Koto Baru, Solok Regency, between 2017 and 2025. The research is motivated by Yusrizal’s success as a young entrepreneur who managed to develop a batik business rooted in local wisdom amidst industry competition, while simultaneously contributing to the preservation of Minangkabau culture. The study aims to describe Yusrizal’s journey as a batik entrepreneur and analyze the strategies he employed to develop Batik Tulis Salingka Tabek. It utilizes the historical method, encompassing heuristics, source criticism, interpretation, and historiography. Data were gathered through literature reviews, observation, documentation, and interviews with Yusrizal and informants associated with the business's development. The findings indicate that the success of Batik Tulis Salingka Tabek was driven by motif innovations that highlight the cultural identity of Solok Regency, the use of digital media and exhibitions as marketing strategies, the strengthening of government networks, and the empowerment of the local community in the production process. This business has not only enhanced the competitiveness of Solok’s signature batik but has also impacted job creation, improved the local economy, and fostered the preservation of local culture. The study demonstrates that developing creative industries based on local wisdom can be an effective strategy for strengthening regional cultural identity while supporting sustainable community economic development.